The effect of environmental enrichment on sun bear (Herlarctos malayanus) behaviour in captivity - Siti Sarayati Abdul-Mawah,; Y. Norma-Rashid,; Ramli R., (Penerbit Universiti Kebangsaan Malaysia, 2022)
One of the main concerns for animals kept in captivity is expression of stereotypic behaviour which could indicate stress in the animals. To ensure the welfare of animals are adequate for conservation and to promote species specific behaviour that similar to those in the wild, most of zoos are implementing environmental enrichment. The effect of environmental enrichment on behavioural changes was studied in seven captive sun bears kept in an enclosure at Zoo Negara, Kuala Lumpur, Malaysia. Bear behaviours are divided into three categories: Active, passive, and abnormal behavioural. The study involved three period: baseline, enrichment, and post-enrichment period. The activity budget was recorded as a single animal scan. A total of 210 h of baseline data was collected over 36 weeks at varying times of days. Three different environment enrichment tools were used; buoy with dog food, hidden fruit mixed with honey, and gunny sack filled with cinnamon powder. They were installed in the enclosures for 10 consecutive days on a rotational basis. Both enrichment and post-enrichment observations were done for 210 h using the same methods as in baseline sampling. Baseline data showed greater passive and abnormal behaviours than active behaviour. With the introduction of the enrichment tools, the sun bears displayed decreased passive and abnormal behaviours with an increment of active behaviour. For post-enrichment period, there was no significant difference when compared with the baseline between all behavioural categories. Among three enrichment tools, hidden fruit mixed with honey was the most preferred enrichment followed by buoy filled with dog food and gunnysack with cinnamon powder. It is suggested that food-based enrichment should be lasting until evening for the sun bear to engaged longer to the enrichment. Although less preferred, cinnamon powder introduction as sensory enrichment was recommended as well. However, it is crucial to ensure that the cinnamon’s odour lasting until late evening, where the bears are ready to enter their night den. It can be concluded that the application of various enrichment tools may help to alleviate abnormal behaviour in captive bears.